DAMPAK HOSPITALISASI TERHADAP PERKEMBANGAN ANAK - Utami, Yuli (Jurnal Ilmiah Widya, 2014)
Hospitalization in children is a stressful experience for both the children themselves and their parents. The hospital environment can be a cause of stress and anxiety in children. The number of stressors experienced by children when undergoing hospitalization interfere adversely affecting the child's development. In line with the increase in the number of children who were hospitalized late population at risk of an increase in children who have developmental disorders. This research aims to identify and discuss in more detail discuss about: (1) stressors of hospitalization (2) the child's response when undergoing hospitalization (3) the family's response to hospitalization (4) Impact of hospitalization (5) Minimize the impact of hospitalization. The method of this paper is the study of literature with descriptive exploratory approach. It can be concluded that there are stressors in the hospital will be faced by children when undergoing hospitalization, with limited coping owned subsidiary raises a variety of responses when faced with stressors that exist, the family is the smallest unit that is very vulnerable affected by the presence of hospitallisasi, negative impact on the development of children at risk appear and require proper handling, planned and organized.